Zero Feet Away: The Digital Geography of Gay Social Media. Issue 3 (3rd March 2016) - Roth, Yoel
ABSTRACT: For this contribution to the "Cartographies" section of the special issue on "Mapping Queer Bioethics, " the author focuses on the terrains of digital media, geosocial networking, and sexually based social media in LGBT communities. Addressing the communal potentials and ethical complications of geosocial connections made possible by such sexually based social media, the author asks whether digital forms of cartography via applications such as Grindr and Scruff simplify, complicate, or merely expose historically longstanding notions of queer interconnectivity.